Jinkui Shenqi Pills Ameliorate Asthma with “Kidney Yang Deficiency” by Enhancing the Function of the Hypothalamic-Pituitary-Adrenal Axis to Regulate T Helper 1/2 Imbalance - Ji, Bing (Evid Based Complement Alternat Med, 2018)
The aim of the study was to investigate the effects and underlying mechanism of JKSQP in a rat model of asthma with kidney-yang deficiency (KYD). Materials and Methods. Hydrocortisone (HYD) was used to establish the rat model of KYD; rats were then sensitized and challenged with ovalbumin (OVA). JKSQP was administered to OVA-challenged rats, and the changes in signs and symptoms of KYD were observed. The leukocyte number and subpopulations in bronchoalveolar lavage fluid (BALF) were counted and the cells were stained with Wright–Giemsa dye. Serum adrenocorticotropic hormone (ACTH), corticosterone (CORT), corticotropin-releasing hormone (CRH), total immunoglobulin E (IgE), and OVA-specific IgE levels were determined using relevant enzyme-linked immunosorbent assays (ELISA) kits. Results. JKSQP not only reversed the phenomenon of KYD but also significantly inhibited the number of leukocyte and eosinophils in the BALF, increasing the level of interferon (IFN)-γ and decreasing the levels of interleukin-4 (IL-4) and IgE in the serum compared with the OVA-challenged groups. Conclusions. Taken together, the antiasthma effects of JKSQP were likely mediated by the enhancement of the function of the hypothalamic-pituitary-adrenal axis and the reversal of T helper 1/2 imbalance.